Post-Surgical Quality of Life, Psychological State and what Patients Think about the Effectiveness of Heller Myotomy in the Treatment of Achalasia - Telma Vale-Fonseca; Luis Ferreira-Pinto; Margarida Figueiredo-Braga; Silvestre Carneiro (Acta Médica Portuguesa, 2016)
Introduction: The disruption of esophageal motility that characterizes achalasia typically provokes dysphagia, pain, loss of weight and malnutrition. Therefore, patients frequently report a reduction in quality of life and negative emotional states. Laparoscopic Heller myotomy proved to be an effective therapy, enabling the resumption of good quality of life. Material and Methods: The authors studied 45 patients previously submitted to laparoscopic Heller myotomy. Postoperative evaluation was performed using a customized version of the achalasia disease-specific quality of life questionnaire. Quality of life and the presence of depressive and anxiety symptoms were assessed using the Portuguese versions of the Medical Outcomes Study SF-36 and the Hospital Anxiety and Depression Scale. Results: Thirty-one patients responded to the survey. Dysphagia was the main clinical symptom before surgery. A clear improvement in dysphagia, regurgitation, pain and weight loss was found after surgery (p < 0.001). The Mental Health domain of SF-36 presented a Pearson correlation coefficient of -0.689 with HADS-D and of -0.557 with HADS-A (p < 0.001 and p = 0.002, respectively). Conclusion: This study demonstrates that the Heller myotomy is associated with a good quality of life in patients with achalasia and strengthens the evidence that this is a safe and reliable procedure.